The Productivity and Income Analysis of Corn Farming in Lalodati Sub-District Puuwatu District Kendari City - Indah Ihdhinashta; Lukman Yunus; Munirwan Zani (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
This study aims to determine the productivity of corn farming, the influence of land area, the amount of use of seeds, fertilizers, herbicides, and labor on the productivity of corn farming, as well as the income of corn farming in Lalodati Village, Puuwatu District, Kendari City. This research was conducted from June to August 2022. Determining the number of samples in this study used the Census Method, so the respondents were 25 farmers. The data analysis used is the method of productivity analysis and income analysis. The results showed that the average productivity of corn farming was 1,867 kg/ha/planting season. In contrast, the average income earned by farmers is IDR 5,184,283/per planting season.